Evaluación de sistemas de manejo con base a la agricultura de conservación para adaptación al cambio climático en la Granja Laguacoto III, cantón Guaranda, Ecuador - Chicaiza Chicaiza, Bladimir Alexander (2020)
The maize cultivation is of great global importance for its contribution to food security and sovereignty. In the high lands of Ecuador and therefore in Bolívar province, it is the main component of the production system due to its direct relationship with natural, social, cultural, economic and environmental capitals. However, due to the conventional agriculture model with the irrational use of agricultural machinery under hillside conditions, intensive monocultures, genetic erosion processes, and deterioration in soil quality and due to climate change droughts, pest insects, diseases and highly harmful weeds are factors that have put food security and sovereignty at high risk. In view of this threat, it is essential to initiate Conservation Agriculture (CA) processes, which contribute to the sustainability of agriculture by the principles of minimal soil removal, rotation of crops in a biological and market function and the management of biomass. Bolívar province is the largest producer of soft maize in Ecuador with 38,000 ha, but is threatened by conventional agriculture with high dependence on external supplies. This research was carried out at the Laguacoto III Experimental Farm, which is at an altitude of 2640 m, with a type of clay franc soil and low organic matter content. This CA process began in 2016 and this research corresponds to 2019 year. The objectives set out were: (i) To evaluate the effect of five technological alternatives for the production of soft maize INIAP - 111, (ii) To measure the effect of eight technological alternatives on the main indicators of soil chemistry, (iii) Performing the Partial Budget Economic Analysis (AEPP) and calculate the Marginal Rate of Return (TMR) and (iv) Select technology alternatives that are resilient to climate change. Eight treatments were evaluated including conventional and conservation agriculture, crop rotation and plant remains management. An experimental design of Full Random Blocks was applied with three repetitions. Variance analyses, Tukey test, complete analysis of soil chemistry were performed before and at the end of the two depth test. At the end of the fourth year of research, there were significant differences in yields of INIAP - 111 variety maize and rotation crops such as Line A2 durum wheat and INIAP 480 shrub beans. The content of Organic Matter (OM) in CA treatments increased significantly and therefore the quality of the soil reflected through the indicators: C/N ratio, C fixation, macro and microorganism biodiversity and Cationic Exchange Capacity. In conventional farmer technology (Control) the pH tends to become acidic and presented the lowest OM content. Significant differences were determined between soil chemistry contents at the two depths evaluate. Finally, this research was able to select and consolidate valid technological alternatives to improve the sustainability of local soft maize production systems through the three fundamental principles of CA such as the minimal removal of the soil; management of plant remains and crop rotation with wheat and beans.